Potret Perilaku Menyimpang Remaja Dalam Novel Lelaki Harimau Karya Eka Kurniawan - Rully Angga Pranadiska; Muhammad Ismail Nasution (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to determine the forms of adolescent deviant behavior in the novel Lelaki Harimau by Eka Kurniawan, the factors that cause adolescent deviant behavior, and the impact of adolescent deviant behavior in the novel Lelaki Harimau. This research uses the theory of literary sociology studies. This type of research is literary research using descriptive methods. The data source used is the novel Lelaki Harimau by Eka Kurniawan. The results of this research are forms of deviant behavior, namely (a) drug abuse, (b) imperfect socialization process, (c) prostitution, (d) sexual deviation, (e) criminal acts, and (f) lifestyle. There are seven types of causes of adolescent deviant behavior, namely, (a) unhealthy mental attitude factors, (b) family disharmony, (c) factors that vent feelings of disappointment, (d) environmental factors, (e) the perpetrator has a sense of wanting to be praised, (f) the perpetrator undergoes a deviant learning process, (g) the perpetrator is unable to absorb norms. There are six types of impact of adolescent deviant behavior, namely (a) isolation, (b) disruption of mental development, (c) guilt, (d) crime, (e) fading of values and norms, and (f) disruption of social balance. The research results are as follows.